2009
DOI: 10.1097/prs.0b013e3181addb8f
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Lasso, Pulvertaft Weave, and Side-by-Side Tendon Repairs

Abstract: The strength of the lasso tendon repair compared well with the Pulvertaft weave and was more convenient to perform. Side-by-side repair was inferior because of its low maximum load. This study suggests that lasso repair may be an alternative to the Pulvertaft weave in tendon grafts and transfers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 17 publications
0
47
2
4
Order By: Relevance
“…Nevertheless, the lasso weave is at a disadvantage, because it is a thick weave, which means it is not usable in spacerestricted areas such as zone II injuries. 1 In the same article, they also tested the side-by-side repair, but it had a significantly lower maximum load, showing it to be inferior to the PW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the lasso weave is at a disadvantage, because it is a thick weave, which means it is not usable in spacerestricted areas such as zone II injuries. 1 In the same article, they also tested the side-by-side repair, but it had a significantly lower maximum load, showing it to be inferior to the PW.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The spiral linking technique does however solely rely on the sutures made to hold both twisted tendons together instead of on the strength of the tendon itself. 1 There is also the lasso weave, which is more convenient to perform and needs less tendon length to perform a repair than the PW. Concerning force measurements, both weaves are similar.…”
Section: Discussionmentioning
confidence: 99%
“…4). 33 The authors believed that the lasso technique was easier to perform than the Pulvertaft weave and found it to be as strong as the weave, but like the double loop, it was considerably thicker. Finally, Brown et al used a new side-to-side coaptation technique and demonstrated that it was substantially stronger than the weave, and no bulkier (Fig.…”
Section: Tendon Coaptationmentioning
confidence: 98%
“…A Pulvertaft weave [14] was used with semitendinosus allograft at the distal peroneus brevis insertion site. This was then weaved in Pulvertaft fashion proximally to the tendon and then distally to the peroneus longus stump (Fig.…”
Section: Case Presentationmentioning
confidence: 99%